2019
DOI: 10.1002/jmri.26865
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast‐enhanced and diffusion‐weighted MRI of invasive breast cancer for the prediction of sentinel lymph node status

Abstract: Background Although sentinel lymph node biopsy (SLNB) is the current standard for identifying lymph metastasis in breast cancer patients, there are complications of SLNB. Purpose To evaluate preoperative dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) and diffusion‐weighted imaging (DWI) of invasive breast cancer for predicting sentinel lymph node metastasis. Study Type Retrospective. Population In all, 309 patients who underwent clinically node‐negative invasive breast cancer surgery Field Stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 37 publications
(78 reference statements)
2
37
0
Order By: Relevance
“…It can provide more metabolic and biological information than conventional imaging methods (17). Previous studies have shown that radiomic features derived from MRI or computed tomography (CT) data have the potential to predict LN metastasis in such malignancies as breast cancer, cervical cancer, and bladder cancer (18)(19)(20). For the rectal cancer, some previous studies demonstrated that the histogram features from T2-weighted imaging (T2WI) and the texture features from apparent diffusion coefficient (ADC) maps can help predict lymph node metastasis (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…It can provide more metabolic and biological information than conventional imaging methods (17). Previous studies have shown that radiomic features derived from MRI or computed tomography (CT) data have the potential to predict LN metastasis in such malignancies as breast cancer, cervical cancer, and bladder cancer (18)(19)(20). For the rectal cancer, some previous studies demonstrated that the histogram features from T2-weighted imaging (T2WI) and the texture features from apparent diffusion coefficient (ADC) maps can help predict lymph node metastasis (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…In the published literature to date [ 6 , 76 , 77 , 78 , 80 , 81 , 82 , 83 , 84 , 85 ] radiomics has been found to have moderate to good diagnostic accuracy for the determining the nodal status (AUC 0.60–0.90) in patients with BC.…”
Section: Prediction Of Lymph Node Metastasesmentioning
confidence: 99%
“…In some studies [ 6 , 81 , 82 , 83 ], the prediction using a combination of radiomics features and clinical risk factors led to further improvement in the identification of nodal status. Particularly, Dong et al [ 82 ] showed how radiomics features extracted from DWI sequences were highly correlated with ALN metastases than those extracted from ADC.…”
Section: Prediction Of Lymph Node Metastasesmentioning
confidence: 99%
“…In addition to the tissue concentrations over time, the quantitative kinetic parameters were also extracted from the TICs. The initial percentage enhancement (E 1 ), peak percentage enhancement (E peak ), and signal enhancement ratio (SER) were calculated as follows [27]:…”
Section: Quantitative Kinetic Parametersmentioning
confidence: 99%
“…Most DCE-MRI studies have focused on measuring the intra-tumoural and background parenchymal features in individual two-dimensional (2D) slices with manually drawn ROIs [12][13][14]. More recently, it has been suggested that features extracted from peri-tumoural tissues could offer additional markers by reflecting angiogenic activity [15].…”
Section: Introductionmentioning
confidence: 99%